# Simple Equation

## Exercise 4.3

Question 1: Solve the following equations:

(a) 2y+5/2=(35)/(2)

Answer: 2y+5/2=(35)/(2)

Or, 2y=(35)/(2)-5/2

Or, 2y=(35-7)/(2)=(28)/(2)=14

Or, y=(14)/(2)=7

(b) 5t+28=10

Answer: 5t+28=10

Or, 5t=10-28=-18

Or, t=-(18)/(5)=-33/5

(c) a/5+3=2

Answer: a/5+3=2

Or, a/5=2-3=-1

Or, a=-1xx5=-5

(d) q/4+7=5

Answer: q/4+7=5

Or, q/4=5-7=-2

Or, q=-2xx4=-8

(e) 5/2x=10

Answer: 5/2x=10

Or, x=10xx2/5=4

(f) 5/2x=(25)/(4)

Answer: 5/2x=(25)/(4)

Or, x=(25)/(4)xx2/5=5/2=21/2

(g) 7m+(19)/(2)=13

Answer: 7m+(19)/(2)=13

Or, 7m=13-(19)/(2)

Or, 7m=(26-19)/(2)=7/2

Or, m=7/2÷7=1/2

(h) 6z+10=-2

Answer: 6z+10=-2

Or, 6z=-2-10=-12

Or, z=-(12)/(6)=-2

(i) (3l)/(2)=2/3

Answer: (3l)/(2)=2/3

Or, 3l=2/3xx2=4/3

Or, l=4/3÷3=4/9

(j) (2b)/(3)xx5=3

Answer: (2b)/(3)xx5=3

Or, (2b)/(3)=3/5

Or, b=3/5xx3/2=(9)/(10)

Question 2: Solve the following equations:

1. 2(x + 4) = 12

Answer: 2(x + 4) = 12
Or, x + 4 = 12 ÷ 2 = 6
Or, x = 6 – 4 = 2
2. 3(n – 5) = 21

Answer: 3(n – 5) = 21
Or, n – 6 = 21 ÷ 3 = 7
Or, n = 7 + 6 = 13
3. 3(n – 5) = - 21

Answer: 3(n – 5) = - 21
Or, n – 5 = - 21 ÷ 3 = - 7
Or, n = - 7 + 5 = - 2
4. – 4(2 + x) = 8

Answer: – 4(2 + x) = 8
Or, 2 + x = 8 ÷ ( - 4) = - 2
Or, x = - 2 – 2 = - 4
5. 4(2 – x) = 8

Answer: 4(2 – x) = 8
Or, 2 – x = 8 ÷ 4 = 2
Or, x = 2 – 2 = 0

Question 3: Solve the following equations:

1. 4 = 5(p – 2)

Answer: 4 = 5(p – 2)
Or, p – 2 = 4 ÷ 5 = 0.8
Or, p = 0.8 + 2 = 2.8
2. – 4 = 5(p – 2)

Answer: – 4 = 5(p – 2)
Or, p – 2 = - 4 ÷ 5 = - 0.8
Or, p = - 0.8 + 2 = 1.2
3. 16 = 4 + 2(t + 2)

Answer: 16 = 4 + 2(t + 2)
Or, 2(t + 2) = 16 – 2 = 14
Or, t + 2 = 14 ÷ 2 = 7
Or, t = 7 – 2 = 5
4. 4 + 5(p – 1) = 34

Answer: 4 + 5(p – 1) = 34
Or, 5(p – 1) = 34 – 4 = 30
Or, p – 1 = 30 ÷ 5 = 6
Or, p = 6 + 1 = 7
5. 0 = 16 + 4(m – 6)

Answer: 0 = 16 + 4(m – 6)
Or, 4 (m – 6) 0 – 16 = - 16
Or, m – 6 = - 16 ÷ 4 = - 4
Or, m = - 4 + 6 = 2

Question 4: Construct three equations starting with x = 2

Answer: x + 2 = 4
2x + 3 = 7
3x – 2 = 4

Quesiton 5: Construct three equations starting with x = - 2

Answer: 2x – 3 = -7
2x + 4 = 0
5x + 12 = 0